Dinamometer Untuk Alat Uji penarikan Kawat (Perancangan, Pembuatan dan Pengujian) - Sir Anderson - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2018)
The basic principle of metal formation is to change shape by giving an external force so that plastic deformation occurs. One example of this formation is wire drawing. The important parameter in wire drawing is the drawing force, which is the force needed to deform the wire to produce the desired reduction. The measurement of withdrawal force is carried out through a wire drawing test equipped with a dynamometer, which consists of load cell and strain gauge. From this test, the withdrawal force can be measured as an electrical quantity that can be read using a multitester or computer. For wire drawing testing dynamometers are designed and made as measuring sensors for withdrawal forces on a laboratory scale. From the results of testing with a dynamometer the average wire drawing force for copper reduction I was 72.88 kgf, copper reduction II was 95.88 kgf and brass was 126.50 kgf. The price of this test is greater than the theoretical price